Elevated Serum Total Bilirubin Might Indicate Poor Coronary Conditions for Unstable Angina Pectoris Patients beyond as a Cardiovascular Protector - Qi Liang; Yongjian Zhang; Jin Liang (Hindawi-Wiley, 2023)
Backgrounds. Serum total bilirubin (STB) is recently more regarded as an antioxidant with vascular protective effects. However, we noticed that elevated STB appeared in unstable angina pectoris (UAP) patients with diffused coronary lesions. We aimed to explore STB's roles in UAP patients, which have not been reported by articles. Methods and Results. 1120 UAP patients were retrospectively screened, and 296 patients were finally enrolled. They were grouped by Canadian Cardiovascular Society (CCS) angina grades. The synergy between PCI with TAXUS stent and cardiac surgery score (SYNTAX score) and corrected thrombolysis in myocardial infarction flow count (CTFC) were adopted to profile coronary features. The results showed that STB, mean platelet volume (MPV), hs-CRP, fasting blood glucose (FBG), red blood cell width (RDW), and CTFC elevated significantly in the CCS high-risk group. STB (B=0.59, 95% CI: 0.39-0.74, P<0.01) and MPV (B=0.86, 95% CI: 0.42-1.31, P<0.01) could indicate SYNTAX score changes for these patients. STB (≥21.7 μmol/L) could even indicate a coronary slow flow condition (AUC: 0.88, 95% CI: 0.84-0.93, P<0.01). Moreover, UAP patients with elevated STB had a lower event-free survival rate by the Kaplan-Meier curve. STB ≥21.7 μmol/L could reflect a poor coronary flow status and indicate 1-year poor outcomes for these patients (HR: 2.01, 95% CI: 1.06-3.84, P<0.01). Conclusion. Elevated STB in UAP patients has a close relationship with changes in SYNTAX score. STB (over 21.7 μmol/L) could even indicate a coronary slow flow condition and poor outcomes for the UAP patients.